E-Learning Content Development as a Training Optimization Effort at PT. Summarecon Agung, Tbk - Muhammad Hafizh Alfaridzi; Arton Briyan Prasetio; Vita Briliana; RR. Niken Purbasari (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2022)
This report contains the author's activities while participating in Magang Bersertifikat Kampus Merdeka program initiated by the Ministry of Education, Culture, Research, and Technology, the main objective of this program is to provide direct work experience mentored by practitioners who are experts in their fields. In this report, the author will explain about the company, daily activities carried out include training administration and also projects regarding e-learning content development and the learning management system during participation as part of the corporate training division at PT Summarecon Agung Tbk. As a result of this program, the author was able to develop competencies from a technical point of view which includes administration, learning management system operation and e-learning content production for non-technical competencies development which include teamwork, problem solving, communication and adaptability in the workplace.